â€œPENGARUH CONTRACT CHANGE ORDER PADA KONSULTAN SUPERVISI TERHADAP BIAYA DAN WAKTUâ€ - MA'RIFAH, RUSMA FATIMAH (KURVA S JURNAL MAHASISWA, 2020)
In various construction projects often change order or request change. Change order can occur during the construction project and cannot be avoided. The occurrence of change order on construction projects often have a negative impact that can affect project costs and time. This study aims to determine the effect of change order on supervision consultants on cost and time, because not only are executing contractors undergoing change order, supervisory consultants also often experience change order.This research begins with data retrieval related to the project in the supervision consultant. Furthermore, the data is analyzed and a legal basis study related to contract changes. The result is the effect of change order on the supervision consultant is the loss experienced by the supervision consultant both in terms of losses in terms of costs and losses in terms of time. Based on the analysis of the legal basis, through Presidential Regulation Number 16 of 2018 and Circular Letter of the Director General of Highways Number 02 / SE / Db / 2016 the state regulates the addition of a contract value of a maximum of 10% if a contract change occurs, and the data allocation can be taken from the ceiling the activity concerned.